Patterns for semantic human behavior analysis - Castillo, David (2018)
The research conducted in recent years that are described in the next section were used as a basis for the research tasks of this thesis proposal where the objective is to investigate and use adaptive techniques to analyze videos detecting semantic patterns of human behavior. Make an analysis in the analysis of scenes in order to classify contexts and track the objects presented in a video. The fact that you are ready for the exam is what the object of study has to do in a given context and compares what you really should do. Although the results of these investigations can be applied in multiple contexts, and especially its technological transfer to the area of health. In particular, we work with information related to the body movements of people with Alzheimer's. According to the opinion of the specialized medical professionals, the corporal movements are modified as the disease progresses. Therefore, the result of this type of change is the way in which the benefits of the corresponding medical treatment are increased. © 2018 AISTI.